1998
DOI: 10.1074/jbc.273.11.6312
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Complex of Maclura pomiferaAgglutinin and the T-antigen Disaccharide, Galβ1,3GalNAc

Abstract: Maclura pomifera agglutinin is a tetrameric plant seed lectin with high affinity for the tumor-associated T-antigen disaccharide, Gal␤1,3GalNAc␣, and hence for many O-linked glycopeptide structures. Unlike members of most lectin families, it lacks both metal ions and Cys residues. The structure of its complex with Gal␤1,3GalNAc was determined to 2.2 Å by first using multiwavelength anomalous diffraction with a lead derivative of the native protein, and then using molecular replacement with the unrefined struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(85 citation statements)
references
References 28 publications
(37 reference statements)
2
83
0
Order By: Relevance
“…Gal binding and broader specificity of gJRLs is believed to be due to co-/posttranslational processing of their precursor polypeptide chain, which generates a larger ␣-chain and a smaller ␤-chain (27). The amino group of Gly at the newly created N terminus (␤-chain) has been shown to interact with O-4 of Gal and is believed to confer galactose-binding specificity to jacalin and MPA lectins (19,24). Astoul et al (44) proposed that the differ- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Gal binding and broader specificity of gJRLs is believed to be due to co-/posttranslational processing of their precursor polypeptide chain, which generates a larger ␣-chain and a smaller ␤-chain (27). The amino group of Gly at the newly created N terminus (␤-chain) has been shown to interact with O-4 of Gal and is believed to confer galactose-binding specificity to jacalin and MPA lectins (19,24). Astoul et al (44) proposed that the differ- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the carbonyl of Glu 36 is in contact with the nitrogen of Arg 38 of the other monomer and vice versa. Another important contact is established between the side chains of Arg 38 and Asp 35 of the other monomer. Overall, these interactions appear to be less extensive than those observed within the dimer in the asymmetric unit (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to these hydrogen bonds between the two strands, another contact is established between the side chains of Glu 22 of one chain and Asn 25 of the other. Another contact is established between strand B of one monomer and strand C of the other sheet in the other monomer: the side chains of Arg 19 in one monomer and Asp 35 of the other monomer are in contact with each other. These contacts between monomers force the two Arg 23 residues into positions that are quite close to one another (and also very close to the non-crystallographic dyad), but the positive charges of the arginines are neutralized by those of the two Glu 36 of the same monomer.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the affinity towards T antigen is often enhanced by its clustering at the surface of tumor cells [39] (this holds also true for the Tn-antigen!!!). X-ray analysis of the corresponding lectin-T antigen-complexes demonstrated that the carbohydrate-binding site of the Maclura pomifera agglutinin (MPA) (PDB code 1JOT) [40] and jacalin from Artocarpus integrifolia (PDB code 1M26) [41], which both belong to the family Moraceae, accommodate the T antigen disaccharide in a similar way (Fig. 2D,E).…”
Section: Structural Requirements For the Binding Of T Antigen To mentioning
confidence: 95%